The antenna DSA 3 and its potential use for Radio Astronomy - Benaglia, Paula (2011)
The European Space Agency (ESA) will inaugurate its third Deep Space Antenna (DSA 3) by the end of 2012. DSA 3 will be located in Argentina near the city of Malarg"ue in the Mendoza province. While the instrument will be primarily dedicated to communications with interplanetary missions, the characteristics of its antenna and receivers will also enable standalone leading scientific contributions, with a high scientific-technological return. We outline here scientific proposals for a radio astronomical use of DSA 3.